Phytochemical content, toxicity and antioxidant activities of native medicinal plants from North Sumatra. Issue 1 (November 2020) - Pasaribu, G; Waluyo, T K; Winarni, I
Abstract: Sumatra Island, one of the major islands in Indonesia, has a high biodiversity of medicinal plants. The objective of the study was to identify and analyze the phytochemical content, toxicity, and antioxidant activity of ten medicinal plant species from North Sumatra. To find out the group of compounds, The plants were screened the presence of phytochemicals i.e. tannins, saponins, flavonoids, triterpenoids, alkaloids, and hydroquinones. Antioxidant activity was measured by 2, 2-diphenyl-1-picryl-hydrazyl radical (DPPH). Results showed that the local people used the medicinal plant for various diseases or disorders such as stomach ache, fever medicine, fractures medicine, stomach ulcers, diuretic, and antidiabetic. The phytochemical testing showed that the extract contains flavonoids, saponins, tanin, and alkaloids. All medicinal plants are classified as toxic and have the potential as raw materials for medicines. The antioxidant activity (IC50 ) were Sikkam 27, 06 ppm; Modang Kulim 104, 81 ppm; Handis 35, 38 ppm; Rugi-rugi 45, 70 ppm; Sambang-sambang 207, 63 ppm; Ampapaga 58, 97 ppm; Sae-sae putih 53, 19 ppm; Sae-sae hitam 41, 08 ppm; Pirdot 146, 40 ppm and Sirungguk more than 250 ppm. In general, the antioxidant activity of ten medicinal plant species studied has good activity. These plant species have the potential to be developed into standardized herbal medicines.